The Role of Teamwork and Work Environment on Employee Performance through Job Satisfaction at the Demak Regency Regional Health Service - Anis Riskiyani; Alifah Ratnawati (eCo-Buss, 2025)
This study analyzes the influence of Teamwork and Work Environment on Employee Performance and examines the role of Job Satisfaction as an intervening variable at the Demak District Health Office. The approach used is quantitative with PLS-SEM analysis on 131 respondents. The results of the R-Square test show that Teamwork and Work Environment are able to explain Job Satisfaction by 68.9% and Employee Performance by 69.1%. The Q² value for Job Satisfaction (0.671) and Employee Performance (0.598) indicates a strong predictive ability of the model. The examination of direct effects reveals that both Teamwork and the Work Environment positively and notably influence Job Satisfaction and Employee Performance. Additionally, Job Satisfaction itself significantly impacts Employee Performance. The analysis of indirect effects demonstrates that Teamwork (p = 0. 003) and the Work Environment (p = 0. 001) significantly affect Employee Performance, with Job Satisfaction acting as a mediator. This finding confirms that a conducive work environment and good teamwork increase job satisfaction and have an impact on improving employee performance.